2002
DOI: 10.3310/hta6230
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and economic evaluation of pegylated liposomal doxorubicin hydrochloride for ovarian cancer

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 16 publications
(26 reference statements)
0
17
0
Order By: Relevance
“…These included the two previous HTA reports that this review updates. 38,39 One of the previous reports was on the use of PLDH 38 and the other on the use of topotecan.…”
Section: Systematic Reviews/meta-analysismentioning
confidence: 99%
See 4 more Smart Citations
“…These included the two previous HTA reports that this review updates. 38,39 One of the previous reports was on the use of PLDH 38 and the other on the use of topotecan.…”
Section: Systematic Reviews/meta-analysismentioning
confidence: 99%
“…The first of these reviews was a previous HTA report on the effectiveness of PLDH. 38 The report had included the trial of PLDH versus topotecan included in the present review. 22 The previous report concluded that, overall, there were no statistically significant differences between PLDH and topotecan with regard to the main clinical outcomes.…”
Section: Other Related Systematic Reviewsmentioning
confidence: 99%
See 3 more Smart Citations